Perancangan Treatment Risiko Pada Proses Produksi Di Cv. Bearpath Untuk Memenuhi Persyaratan Iso 9001:2015 Klausul 6.1 dengan Pendekatan ISO 31000:2018 - Rizki Eka Ridani; Sri Widaningrum; Heriyono Lalu (eProceedings of Engineering, 2019)
Abstractâ”€â”€ Based on ISO 9001: 2015 clause 6.1 CV.Bearpath must consider the risks in producing mountain shoes, so as to minimize and reduce the impact of these risks, and can determine the mitigation measures in advance. Therefore the purpose of this study is to carry out a risk assessment based on ISO 31000: 2018 in the mountain shoe production process at CV.Bearpath. The data used in this study are in the form of existing company conditions, internal issues and external issues, and requirements for ISO 9001: 2015 clause 6.1. Based on the risk register results, there are 4 risks that have a medium level and also a high level, 4 risks that require a handling action will be given a risk treatment plan in the form of mitigation planning and contingency planning, but the risk that has a high level will be designed. In this study, the risk that will be designed for treatment is late material purchases that have a high risk level, the design to be carried out in the form of an SOP. The SOP has considered the risk register and the results of the gap analysis. Keywords: ISO 9001: 2015, Production, ISO 31000: 2018, Risk Assessment, Risk Register, Treatment